Yielding tourists' preferences - Serra, Jaime (2015)
This chapter uses stated tourist preferences as a proxy of visitor yield measures, in order to analyse and understand the yield potential of different markets' preferences. A literature review revealed that there is much progress to be made in terms of discussion, consensus and stability of methodology for the measurement of visitor yield. The aim of the visitor yield analysis, in the current chapter, is also to bring another dimension into yield analysis and discussion, contributing with a new form of measuring yield potential. Since the objective is to identify yield patterns based on tourist preferences over a period of time, dynamics may be captured from the fluctuation patterns, or expressed as volatility of visitor yield and length of stay throughout the years. Destination management organisations and tourist companies may potentially adopt this visitor yield matrix in order to support future strategic decisions.